高周波電気的膜破壊（ＲＦ-ＥＭＢ）による癌免疫療法 (2016)
【課題】完全かつ即座の細胞膜破裂及び破壊を引き起こすために十分なエネルギーのパルスの、両極性の、瞬時の荷電反転電界の適用によって、体内の望ましくない組織の非熱的アブレーションの方法を提供する。【解決手段】本発明において、エネルギーは、特定の周波数、波長特性、パルス幅及びパルス数の高周波パルスを介して送達される。その結果、増強された物理的応力が、細胞膜上に付与され、その即座かつ完全な破壊を生じ、それによって、細胞内容物及び膜構成要素全体を、タンパク質を変性させることなく、細胞外空間内に流出させ、生体内の至る所の標的組織及び特異な組織を破壊及び除去するための免疫学的応答を可能にする。【選択図】図９ A method of non-thermally ablating undesirable tissue in the body by application of pulsed, bipolar, instant charge reversal electrical fields of sufficient energy to cause complete and immediate cell membrane rupture and destruction. Energy is delivered through radio frequency pulses of particular frequencies, wave characteristics, pulse widths and pulse numbers, such that enhanced physical stresses are placed on the celt membrane to cause its immediate and complete destruction thereby spilling the entire cell content and membrane constituents into the extracellular space without denaturing proteins so as to enable an immunological response to destroy and remove the target tissue and similarly marked tissue elsewhere in the subject.